Noiseless Variable-Pressure Neck Chamber Device to Assess the Carotid Baroreflex Function - Pinheiro, Alessandro; Vianna, Lauro C.; Carmo, Jake C. (Frontiers in Physiology, 2021)
Background: The blood pressure responses to baroreflex perturbations can be assessed only using the variable-pressure neck chamber technique. However, the application of this approach in hospital environments is limited owing to the loud noise emitted during its operation. This study was aimed at developing a noiseless neck suction chamber device (NCD) that could stimulate the baroreceptors located in the carotid sinus in humans. Methods: A non-invasive device was developed to pressurize the carotid arteries externally. A microcontroller with a computer interface and neck chamber (3D-printed) was used. The anatomical neck chamber was fitted on six healthy, young, asymptomatic participants (five men; 32 ± 6 year), who were normotensive, nonsmoking, in sinus rhythm, free of known cardiovascular or metabolic diseases, and not consuming any acute or chronic medications. A suction of −60 mmHg was applied for 5 s, and the corresponding data were recorded. Before each study visit, the participants were instructed to abstain from caffeine, alcohol, and strenuous exercise for 12–24 h. Results: In all the trials, a significant reflex bradycardia (−10 ± 2 bpm) and depressor response (−15 ± 4 mmHg) to neck suction were observed, consistent with the results in the literature. The neck chamber device operated noiselessly [sound pressure level (SPL) of 34.3 dB] compared to a regular vacuum-cleaner-based system (74.6 dB). Conclusion: Using the proposed approach, consistent blood pressure and heart rate responses to carotid baroreflex hypertensive stimuli could be recorded, as in previous studies conducted using neck collar devices. Furthermore, the neck chamber device operated noiselessly and can thus be applied in hospital environments.